Make your own Angry Birds. (Economist, 2012)
The article focuses on do-it-yourself (DIY) mobile application device creation. Information is provided on DIY application programs such as GameSalad, a gaming creating kit offered by the telecommunications company Research in Motion (RIM), and the program AppMakr. Information is provided on the low costs of DIY application creation and the number of amateur application makers.